Creating genetically modified pigs by using nuclear transfer - Prather Randall S; Lai Liangxue (BMC, 2003)
Abstract Nuclear transfer (NT) is a procedure by which genetically identical individuals can be created. The technology of pig somatic NT, including in vitro maturation of oocytes, isolation and treatment of donor cells, artificial activation of reconstructed oocytes, embryo culture and embryo transfer, has been intensively studied in recent years, resulting in birth of cloned pigs in many labs. While it provides an efficient method for producing transgenic pigs, more importantly, it is the only way to produce gene-targeted pigs. So far pig cloning has been successfully used to produce transgenic pigs expressing the green fluorescence protein, expand transgenic pig groups and create gene targeted pigs which are deficient of alpha-1,3-galactosyltransferase. The production of pigs with genetic modification by NT is now in the transition from investigation to practical use. Although the efficiency of somatic cell NT in pig, when measured as development to term as a proportion of oocytes used, is not high, it is anticipated that the ability of making specific modifications to the swine genome will result in this technology having a large impact not only on medicine but also on agriculture.